Fungsi Kesenian Tari Orang-Orang Bertopeng di Desa Mega Timur Kecamatan Sungai Ambawang Kabupaten Kubu Raya Kalimantan Barat - Andini, Septi Murti (TACET Jurnal Pendidikan dan Kajian Seni, 2023)
The Background of this research is to explore the art function of Masked People"™s dance in Mega Timur Village, sungaiambawang district, Kubu Raya regency, west Kalimantan province. The purposes of this research are 1. To describe the art function of Masked People"™s dance in Mega Timur village, sungai ambawang district, Kubu Raya regency, west Kalimantan province. 2. To describe art performance of masked people"™s dance in mega timur village, Sungai Ambawang district, Kuburaya regency, west Kalimantan province. The researcher uses analysis theories about function, traditional art, traditional dance, art performance, cukture and relevant research. Specifically problems in this research are 1. How about the function of masked people"™s dance in Mega Timur village, Sungai Ambawang district, Kuburaya regency, west Kalimantan province? 2.How about art performance of masked people"™s dance in Mega Timur village, Sungai Ambawang district, Kuburaya regency, west Kalimantan province?. This research uses descriptive method with the form of qualitative research. The research approach uses an anthropological approach. The collecting data in this research is interview result with proper interviewees and know about art performance of Masked People"™s dance in Mega Timur village, Sungai Ambawang district, Kubu Raya regency, west Kalimantan province. Techniques of data collection are observation, interview and documentation, Techniques of data analysis are data reducation, data description and research finding. Techniques of data validity testing uses observation extension technique and triangulation technique.